1989
DOI: 10.1007/bf00392536
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine and putrescine N-methyltransferase in the biosynthesis of tropane alkaloids in cultured roots of Hyoscyamus albus

Abstract: [1,4-(14)C]Putrescine, administered to cultured roots of Hyoscyamus albus L., was converted to spermidine and spermine as well as to conjugated forms. A substantial fraction of its radioactivity (approx. 6%) was, however, incorporated into N-methylputrescine within 4 h, followed by an increase in radioactive tropane alkaloids (mostly hyoscyamine). Incubation of the roots with DL-[5-(14)C]ornithine and L-[2,3-(3)H]arginine separately resulted in rapid incorporation of each label into free putrescine and N-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…These tissues are developmentally young root tissues without secondary growth (12). Putrescine N-methyltransferase (14) and hyoscyamine 6#-hydroxylase (11), other enzymes involved in the biosynthesis of hyoscyamine and scopolamine, are also highly active in the young root tissues. Together with the classical grafting experiments between alkaloid-producing and nonproducing plants (21), and alkaloid formation in organ cultures (13), these results suggest that hyoscyamine and scopolamine are mostly synthesized in the young root cells and translocated to the aerial parts of the plant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These tissues are developmentally young root tissues without secondary growth (12). Putrescine N-methyltransferase (14) and hyoscyamine 6#-hydroxylase (11), other enzymes involved in the biosynthesis of hyoscyamine and scopolamine, are also highly active in the young root tissues. Together with the classical grafting experiments between alkaloid-producing and nonproducing plants (21), and alkaloid formation in organ cultures (13), these results suggest that hyoscyamine and scopolamine are mostly synthesized in the young root cells and translocated to the aerial parts of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in most root cultures the activities of the TRs are generally much higher than those of other enzymes in the pathway: the specific activities of the TRs are in the range of 1 to 1200 pKat/mg of protein, whereas those of putrescine N-methyltransferase (ref. 14 and our unpublished results) and hyoscyamine 6f-hydroxylase (11) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless the results obtained are as disappointing as those obtained overexpressing H6H. The first report of PMT overexpression in hairy roots was with Hyoscyamus albus (Hashimoto et al, 1989). Tracer-feeding studies with radioactive aminoacids demonstrated that putrescine is the precursor of tropane alkaloids.…”
Section: Overexpression Of Key Enzymesmentioning
confidence: 96%
“…It was described by Mizusaki et al (1973) in tobacco for the first time, afterwards it has also been described in Hyoscyamus sp. (Hashimoto et al, 1989, Suzuki et al, 1999. The last part of the tropane alkaloid biosynthetic pathway is the enzymatic reaction catalyzed by hyoscyamine-6β-hidroxylase (H6H), a 2-oxoglutarate dependent dioxygenase (EC 1.14.11.11, MW: 41.000 ± 1.0, optimal pH 7.8) that catalyses the hydroxylation of hyoscyamine to scopolamine in two steps.…”
Section: Biosynthetic Pathway Key Points: Pmt and H6hmentioning
confidence: 99%